Free-standing few-layered graphene oxide films: selective, steady and lasting permeation of organic molecules with adjustable speeds. Issue 4 (24th December 2015) - Huang, Tao; An, Qi; Luan, Xinglong; Zhang, Qian; Zhang, Yihe
Abstract : GO-polyelectrolyte free-standing films selectively permeate molecules with controlled speeds, allowing steady and lasting permeation of molecules for 9 days. Abstract : A variety of small molecules with diameters around 1 nm possess a range of functions, such as antibiotic, antimicrobic, anticoagulant, pesticidal and chemotherapy effects, making these molecules especially useful in various applications ranging from medical treatment to environmental microbiological control. However, the long-term steady delivery (release or permeation) of these small molecules with adjustable and controllable speeds has remained an especially challenging task. In this study, we prepared covalently cross-linked free-standing few-layered GO films using a layer-by-layer technique in combination with photochemical cross-linkages, and achieved a controlled release of positively charged, negatively charged, and zwitterionic small molecules with adjustable and controllable speeds. The steady delivery of the small molecule lasted up to 9 days. Other functionalities, such as graphene-enhanced Raman spectra and electrochemical properties that could also be integrated or employed in delivery systems, were also studied for our films. We expect the special molecular delivery properties of our films to lead to new possibilities in drug/fertilizer delivery and environmental microbiological control applications.